Effectiveness of Augmented Reality-Based Learning Media Towards Elementary School Students' Understanding of Concepts in Science: Systematic Literature Review - Siki, Irene Milenia; Imanuel Herlimus Leba (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study is to investigate the impact of Augmented Reality (AR)-based learning media on students' understanding of science concepts and to evaluate the effectiveness of this media in the Science learning process. The methodology employed is a Systematic Literature Review (SLR). The data collecting technique refers to the PRISMA method utilizing the databases Google Scholar, Open Knowledge Maps, and Publish or Perish (Scopus). This analysis analyzed publications released throughout 2020 until 2024. There were 20 useful articles out of the 428 total. The analytical method employed is descriptive qualitative. The studied indicators include AR-based learning media, elementary school students' understanding of scientific concepts, and the effectiveness of AR-based learning media in enhancing understanding of these concepts. The study's findings indicate that augmented reality improves student understanding of scientific concepts. AR makes learning more fun and encourages students to think critically and solve problems through visualization of interesting material presentation. As a result, students can understand abstract concepts so as to achieve better learning outcomes. Thus, AR-based media is proven effective in improving students' concept understanding. However, the success of AR implementation is highly dependent on the active role of teachers in guiding students and provide sufficient infrastructural support; hence, teachers must receive training on how to use this technology.